2022
DOI: 10.1007/s10461-022-03959-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Adolescent HIV Prevention and Treatment Services in the AHISA Network

Abstract: We investigated perceived impacts of COVID-19 on the delivery of adolescent HIV treatment and prevention services in sub-Saharan Africa (SSA) by administering a survey to members of the Adolescent HIV Prevention and Treatment Implementation Science Alliance (AHISA) from February to April 2021. We organized COVID-19 impacts, as perceived by AHISA teams, under three themes: service interruptions, service adjustments, and perceived individual-level health impacts. AHISA teams commonly reported interruptions to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…5–8 Recorded impacts of the COVID-19 pandemic on the lives of adolescents include prolonged school closure, increased economic hardship, social isolation, reduced food intake, increased gender-based violence, and an uptick in teenage pregnancy. 9–12 Furthermore, many adolescents have experienced negative mental health outcomes as a result of COVID-19, with decreased access to psychosocial support. 13–15 In addition, findings from South Africa and the United States demonstrate that ALHIV on treatment experienced increased vulnerabilities during the pandemic, including economic loss, food insecurity, and treatment interruptions.…”
Section: Introductionmentioning
confidence: 99%
“…5–8 Recorded impacts of the COVID-19 pandemic on the lives of adolescents include prolonged school closure, increased economic hardship, social isolation, reduced food intake, increased gender-based violence, and an uptick in teenage pregnancy. 9–12 Furthermore, many adolescents have experienced negative mental health outcomes as a result of COVID-19, with decreased access to psychosocial support. 13–15 In addition, findings from South Africa and the United States demonstrate that ALHIV on treatment experienced increased vulnerabilities during the pandemic, including economic loss, food insecurity, and treatment interruptions.…”
Section: Introductionmentioning
confidence: 99%
“…Individual-level impacts included feelings of social isolation, loneliness, loss to follow-up, food insecurity, poverty, and increases in adolescent pregnancies and sexually transmitted infections [10]. Many studies have also reported an increased risk of anxiety, depression, feeling lonely, and a reduction in the quality of life among adolescents during the COVID-19 lockdown because of these stressors [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…A four-point Likert scale provides scores of 0-3 for responses to each item as "not at all", "on several days", "on more than half the days", and "nearly every day", with a summed scores range of 0-21. Summed scores were categorized as minimal symptoms (0-4), mild symptoms (5)(6)(7)(8)(9), moderate symptoms (10)(11)(12)(13)(14) and severe symptoms (15)(16)(17)(18)(19)(20)(21). COVID-19 related anxiety was assessed using a structured questionnaire from Turkey [29].…”
Section: Survey Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on impact of COVID-19 among adolescents by members of the Adolescent HIV Prevention and Treatment Implementation Science Alliance (AHISA) program revealed that the COVID-19 pandemic threatened the accessibility and availability of ART for adolescents [ 31 , 35 ]. The lockdowns restricted access to health care facilities for refills, clinical support such as counselling session and other social support programs [ 27 , 28 , 35 ]. Secondly, healthcare workers were re-deployed in COVID-19 program thus reducing the number of staff members resulting to under-staffing [ 27 , 29 ].…”
Section: Introductionmentioning
confidence: 99%